Pengaruh Pemasaran Online Dan Minat Pelanggan Terhadap Peningkatan Laba Kharisma Studio - Hj. Lis Setyowati Setyowati (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to find out how much influence online marketing and customer interest have in influencing the increase in Kharisma Studio's profits. The type of research conducted is quantitative with the research methods of Validity, Reliability, Classical Assumptions, Multiple Linear Regression, T and F Tests. The data studied were taken using a survey method, using a questionnaire as an instrument of data collection through Google Form. In determining the sample the author uses a simple random sampling technique questionnaire. The respondents were 80 people who had met the specified answer criteria. Based on this research, it is stated that H0 is rejected and H1 is accepted. There is a significant effect between online marketing and customer interest on increasing profits. The result of the contribution of online marketing and customer interest to the increase in profit is 59.3% or 0.593. Where according to the interpretation table the coefficient of determination is included in the medium category.